Note on the variant of "κρυφη" in Exodus 11:2a - Otabela, Claude A. (HTS teologiese studies, 2022)
The spoliation of the Egyptians is an exodus theme whose interpretation is difficult and often controversial. The great cleavage lies between the thesis of a secret and dishonest action and that of an operation of definitive donations within the framework of the expulsion. The addition of the adverb ‘κρυφη’ in the Septuagint has been used to support the exit from Egypt by a secret escape with fraudulently borrowed objects. This article re-evaluates this variant by showing the limits of the status that several critics hastily attributed to it. It, therefore, appears that the choice of the Greek translator corresponds to its own interpretation that does not agree with the source text from which it derives.Contribution: This article contributes to illustrate the overlap between the transmission of the text, its composition and its reception. We also discover how semantic analysis can be decisive in the evaluation of variants in the Septuagint.